Vom Schlafsack bis zur Schwimmweste - Susanne König (21: Inquiries into Art, History, and the Visual, 2022)
This essay examines the mechanisms of the construction of moral meaning on the basis of objects in the field of tension between art and design, whereby the objects in question are morally motivated, insofar as their authors want to contribute, with them, towards improving the living conditions of disadvantaged social groups. The first part discusses Lucy Orta’s Refuge Wear and Bas Timmer’s Sheltersuits, which in their respective designs take into account the needs of homeless people. The second part looks at works on the theme of migration by Hussein Chalayan, Ai Weiwei and Bansky. In choosing these themes and objectives, the artists and designers comply with the moral norm of social responsibility that is currently relevant in art and design. The study will show that an object itself is, and that only the actions performed with the object can be judged in moral terms.